BUSINESS STRATEGY FOR PRIVATE GENERAL HOSPITAL IN UNIVERSAL HEALTH COVERAGE ERA - Nysa Ro Aina Zulfa; Dony Septriana Rosady; Umi Narimawati (JURNAL BISNIS STRATEGI, 2022)
Indonesia seeks to implement Universal Health Coverage to ensure that all people can access health services. The implementation of this program has an impact on the national health system. The pattern of health services has shifted both in terms of health services and health financing. Hospitals as one health care institution must adapt to these changes in order to remain able to provide the best health services. MAL Hospital as one of the hospitals providing health services faces the impact of decreasing income after implementation of Universal Health Coverage. Facing these conditions required the right business strategy for MAL Hospital to be able to increase its income in order to continue running health services as one of the hospital with social mission. This study uses qualitative methods with primary data obtained from interviews and secondary data obtained from reports, articles, journals, and books. In business exploration, this study analyzes and proposes business strategies for public private hospitals. Analysis begins by analyzing internal and external factors. Internal factors are analyzed based on financial, operational, human resources, and marketing aspects. External factors were analyzed using PESTLE Analysis and Porters Force. All factors are classified as Strength, Weakness, Opportunity, and Threat (SWOT). The analysis is continued by calculating the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS). Obtained result value IFAS -40 with value EFAS 20. Position of MAL Hospital by using Cartesian diagram is in quadrant of weakness and opportunity. MAL Hospital should choose competitive strategy through differentiation focus by targeting the main target is the participants of Universal Health Coverage. Some alternative business strategies are prepared using TOWS Matrix. Alternative business strategies were analyzed using Analytical Hierarchial Process to obtain priority program sequence. Priority programs with the highest scores were selected and then continued by organizing activities. Estimated cost required and estimated increase in revenues are calculated to obtain Return on Investment value. MAL Hospital as one of the private hospital that has social mission is expected to do the best business strategy for health service can continue.